A scale-based framework to understand the promises, pitfalls and paradoxes of irrigation efficiency to meet major water challenges. (November 2020) - Lankford, Bruce; Closas, Alvar; Dalton, James; López Gunn, Elena; Hess, Tim; Knox, Jerry W; van der Kooij, Saskia; Lautze, Jonathan; Molden, David; Orr, Stuart; Pittock, Jamie; Richter, Brian; et al.
Graphical abstract: Highlights: Irrigation efficiency is more than a performance indicator or water-savings panacea. Managing irrigation efficiency supports water, food and energy goals. Insufficient understanding of irrigation efficiency may impede policy goals. The meanings and use of irrigation efficiency depend on spatial scale and viewpoint. A matrix of scales and dimensions is proposed to explore irrigation efficiency. Abstract: An effective placement of irrigation efficiency in water management will contribute towards meeting the pre-eminent global water challenges of our time such as addressing water scarcity, boosting crop water productivity and reconciling competing water needs between sectors. However, although irrigation efficiency may appear to be a simple measure of performance and imply dramatic positive benefits, it is not straightforward to understand, measure or apply. For example, hydrological understanding that irrigation losses recycle back to surface and groundwater in river basins attempts to account for scale, but this generalisation cannot be readily translated from one location to another or be considered neutral for farmers sharing local irrigation networks. Because irrigation efficiency (IE) motives, measures, effects and technologies play out at different scales for different people, organisations and purposes, and losses differ from place to place and over time, IE is a contested term, highly changeable and subjective. This makes generalisations for science, management and policy difficult. Accordingly, we propose new definitions for IE and irrigation hydrology and introduce a framework, termed an 'irrigation efficiency matrix', comprising five spatial scales and ten dimensions to understand and critique the promises, pitfalls and paradoxes of IE and to unlock its utility for addressing contemporary water challenges.